Transformed into the same image : constructive investigations into the doctrine of deification - Copan, Paul; Reardon, Michael M. C. (Michael Martin Chester) (Illinois: : IVP Academic, 2024)
"Though the doctrine of theosis has been gaining interest among scholars for some time, most have focused on Roman Catholic or Orthodox traditions. In this constructive account of deification, biblical scholars and theologians focus on the work of major Protestant thinkers and Protestant expressions of the doctrine"--
"The doctrine of deification or theosis has been gaining interest among scholars for some time. Yet most publications on the topic have focused on Orthodox and Roman Catholic traditions and have subsumed the discussion under the category of soteriology. If "being transformed into the same image" (2 Corinthians 3:18) is truly essential to the Christian life, a fuller understanding of this biblical concept is needed for Christians of all traditions.In this volume, biblical scholars and theologians offer a constructive account of deification that breaks new ground in key ways. First, several essays focus on the work of major Protestant thinkers and Protestant expressions of the doctrine-including Lutheran, Reformed, Baptist, Wesleyan, Pentecostal, and Evangelical. Second, contributors incorporate deification into arenas that have thus far remained largely unexplored, such as the relationship between justification and deification, applications for theological education, how deification compares with transhumanism, the impact of translation philosophy on the visibility of deification in Scripture, and perspectives on deification in global Christianity.Contributors include both senior and younger scholars from a variety of backgrounds, including Alister McGrath, Ann Jervis, Veli-Matti Ka||rkka||inen, Ben C. Blackwell, and Michael Gorman. Transformed into the Same Image invites readers to dive deeper into the doctrine of deification and continue the conversation"--
Machine generated contents note: Foreword by Michael J. Gorman -- Introduction-Paul Copan and Michael M. C. Reardon -- Part I: Biblical Foundations -- 1. Conformity to Divine Messiah in Paul (Ann Jervis) -- 2. The Church is Christ: The Wirkungsgeschichte of Interpreting Pauline Soteriology as Ecclesial Deification (Michael M. C. Reardon) -- 3. Deification Seen from Three Biblical Metaphors in Watchman Nee and Witness Lee with a Cognitive-Linguistic Interpretive Approach to Metaphors (Jacob Chengwei Feng) -- 4. Deification and the Eschatological City: Theological Connections in Early Christian Thought (Nathan Betz) -- 5. The Influence of Translation Philosophy upon the Visibility of the Doctrine of Deification in Scripture (Chao-Chun Liu) -- Part II: Protestant Foundations -- 6. Deification or Christification? Martin Luther on Theosis (Alister E. McGrath) -- 7. Deification in the Reformed Tradition from Zwingli to Vermigli (Carl Mosser) -- 8. Jonathan Edwards, Theosis, and the Purpose of Creation (James Salladin) -- 9. John and Charles Wesley on Deification (Mark Gorman) -- 10. C. S. Lewis on Deification (Jahdiel Perez) -- 11. Towards an Evangelical Doctrine of Deification (Paul Copan) -- Part III: New Investigations into the Doctrine of Deification -- 12. Deification as a Theological Foundation and Goal for Formational Theological Education (Brian Siu-kit Chiu) -- 13. Sharing in the Life of God: Considering the Relationship between Justification and Deification (Ben C. Blackwell) -- 14. Justification as Union and Christ's Presence: A Lutheran Perspective (Veli-Matti Ka||rkka||inen) -- 15. Deification and World Christianity: Hesychasm and "Calling upon the Name of the Lord" (Shu-chen Hsu Hsiung) -- 16. Transhumanism as Active Effort of Technology versus Deification as Active Reception of Grace (Kimbell Kornu) -- Contributors.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed
Keywords: Deification (Christianity); Dogma; Religion / Christian Theology / Systematic; Religion / Christianity / Protestant